Topical forms of sertaconazole in the treatment of fungal infections of the skin - E. V. Matushevskaya; E. V. Svyrzhevskaya (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The data of foreign and domestic clinical studies on the efficacy and safety of sertaconazole (SK)is discussed. Broad spectrum of activity of SK and lack of resistance to the drug is established. Several studies opens new opportunities for the SK for the treatment of dermatosis, in the pathogenesis of which play an important role of opportunistic infection. High efficiency and compliance, a significantly greater safety index than that of the other members of the azole group, suggest the SK as a formulation that extends the capabilities of the outer antimycotic therapy of fungal infections of the skin.